Platycodon D reduces obesity and non-alcoholic fatty liver disease induced by a high-fat diet through inhibiting intestinal fat absorption - Xingkui Tang; Xingkui Tang; Yi Yang; Wenxu Peng; Mengping Xu; Qitong Fan; Feng Li; Guorong Zou; Guorong Zou; Jianlin Zhu; Jianlin Zhu (Frontiers Media S.A., 2024)
BackgroundPlatycodin D (PD) has been reported to treat metabolic diseases, including non-alcoholic fatty liver disease. In addition, platycodin D has been reported to activate intestinal 5'AMP-activated protein kinase (AMPK) phosphorylation levels, thereby reducing lipid absorption. Therefore, the aim of this study is to explore whether PD activation of intestinal AMPK and reduced lipid absorption can improve non-alcoholic fatty liver disease.MethodsClean-grade male C57/BL mice were fed a high-fat diet (HFD) (containing 60% calories) for 16 weeks, and oral PD (10 mg/kg/day) was administered at the same time. The liver and intestines were the collected, and the intestines were tested. The expressions of lipid absorption genes (CD36, NPC1L1, and ApoB), the serum total triglyceride (TG) and total cholesterol (TC) levels in the intestines and livers, the fecal free fatty acid (FFA) levels, and the expression of AMPK phosphorylated proteins in the intestines were examined using Western blot analyses. The lipid distribution in the livers, intestines, and fat was detected using Oil Red O and hematoxylin and eosin (H&E) staining. A colon cancer cell line (Caco2) was used to confirm the effect of PD on the cellular lipid uptake in vitro. In addition, serum inflammatory factors and liver enzymes were measured to clarify the impact of PD on the circulation of metabolic syndrome. Leptin-deficient mice (OB) were then used to further explore the improvement of PD on body weight and blood lipids.ResultsPD had a very significant therapeutic or preventive effect on metabolic syndrome and fatty liver induced by a high-fat diet. PD improved body weight, insulin sensitivity, and glucose tolerance in mice fed a high-fat diet and also prevented non-alcoholic fatty liver disease, reduced blood lipid levels, and increased fecal lipid excretion. In addition, PD reduced lipid absorption by activating the intestinal AMPK protein, which may have involved the inhibition of the gene expression levels of intestinal lipid absorption genes (CD36, NPC1L1, and ApoB). The combined effect of these factors improved hepatic lipid accumulation and lipid accumulation in adipose tissue. It was further found that PD also improved the body weights and blood lipid levels of leptin-deficient mice (OB) mice.ConclusionPD had a very strong therapeutic effect on mice under a high-fat diet. PD reduced high-fat diet-induced obesity and non-alcoholic fatty liver disease by inhibiting intestinal fat absorption.